Green Quality Management and Green Target Costing and Their Role in Achieving Competitive Advantage - Durgham Ahmed Abdul Ridha; Islam Ahmed Abdul Ridha; Doaa Ahmed Abdul Ridha (Eximia, 2024)
This study mainly aims at the extent of the possibility of achieving integration between green cost management techniques, including green quality management and green target costing, and the extent of the possibility of achieving many benefits from this integration, including environmental benefits as well as economic benefits for the company and achieving competitive advantage. We have concluded that companies can achieve competitive advantage by adopting the proposed model of integration between green quality management and green target costing, with the use of green value engineering in excluding non-value-adding activities and enhancing value-adding activities, which contributes to enhancing customer value and reducing costs, as well as providing environmentally friendly and differentiated green products.